Correction: Circulating microRNAs as potential biomarkers of early vascular damage in vitamin D deficiency, obese, and diabetic patients. - Adel B Elmoselhi; Mohamed Seif Allah; Amal Bouzid; Zeinab Ibrahim; Thenmozhi Venkatachalam; Ruqaiyyah Siddiqui; Naveed Ahmed Khan; Rifat A Hamoudi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0283608.].